Design Of Electric Switching Systems For Electronic Equipment In Home Based Internet of Thing (IoT) - GOESTI MESKANA PELAWI PELAWI; ACHMAD FAUZI; MILLI ALFHI SYARI (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
The tool for designing an IoT-based electronic equipment switch system has been designed. This system uses the NodeMCU ESP 8266 microcontroller where the NodeMCU ESP8266 functions as a data processor, and also as a receiver for wi-fi networks emitted by wi-fi network systems. This tool system uses a control system using an Android smartphone to turn on and off switches for electronic devices at home, this tool uses a Wi-Fi network communication system so that the device system and Android smartphone can be connected, in this tool system it uses a DC fan and incandescent lamps as outputs. connected to an electrical switch system, and the switch can turn on and turn off electronic devices on designed devices. The smartphone application used in this design is the Blynk application which can be downloaded at Playstore or Google.com. This tool is expected to help and facilitate humans in controlling electronic equipment at home both at home and when traveling.